Review of Sustainable Procurement Systems and Applications in Various Case Studies - Mulyasari, Indah; Darwin, Darwin (UNIVED Press, 2025)
The objective of this research is to explore the determining factors of the sustainable procurement adoption of the public procurement. This strategy could promote facilitate novel knowledge how various elements influence sustainable procurement. This research adopts a systematic literature review strategy to synthesise current bibliographies on sustainable procurement. Findings from synthesis of 33 relevant articles are determinant, role, indicator, conceptual and impact of the sustainable procurement. This research suggests comprising sustainable aspect as a critical element to consider in procurement process beside economic and social aspect. This research contributes to the public procurement literature and the literature on determinants of sustainable procurement